1996
DOI: 10.1111/j.1542-474x.1996.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reproducibility of QT Interval Measurement and QT Dispersion in Patients After Acute Myocardial Infarction

Abstract: Background:The study evaluated interobserver differences in the classification of the T-U wave repolarization pattern, and their influence on the numerical values of manual measurements of QT interval duration and dispersion in standard predischarge 12-lead ECGs recorded in survivors after acute myocardial infarction.Methods: Thirty ECGs recorded at 25 mm/s were measured by six independent observers. The observers used an adopted scheme to classify the repolarization pattern into 1 of 7 categories, based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Previous studies have drawn conflicting conclusions,3 12 13 15 16 which may have arisen because of the various techniques used in these studies and the different populations involved. Van de Loo et al found acceptable reproducibility using manual measurement of QTd both in normal subjects (intraobserver relative error 14%) and in patients with acute myocardial infarction (intraobserver relative error 15%) 3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have drawn conflicting conclusions,3 12 13 15 16 which may have arisen because of the various techniques used in these studies and the different populations involved. Van de Loo et al found acceptable reproducibility using manual measurement of QTd both in normal subjects (intraobserver relative error 14%) and in patients with acute myocardial infarction (intraobserver relative error 15%) 3.…”
Section: Discussionmentioning
confidence: 99%
“…QTID, however, is a poorly reproducible ECG phenomenon with a 30-40% interobserver relative error [3]. For T wave offset alone, the range of variation between two highly qualified experts could be as much as 30.6 ms, in addition to 6.5 ms for the QRS onset [3].…”
mentioning
confidence: 99%
“…For T wave offset alone, the range of variation between two highly qualified experts could be as much as 30.6 ms, in addition to 6.5 ms for the QRS onset [3]. In the study performed by Cupisti et al [2], a single observer blindly performed QTI measurements in 'all possible leads'.…”
mentioning
confidence: 99%
“…23 The fact that only one lead was used in each recording, the annotation of all beats, the similar findings in the analysis of the QT and QaT, the congruence of the findings with the physiological changes at night, and the observed patterns of QT variability in the time, frequency, and chaotic analyses suggest that evaluation of beat-to-beat QT variability is feasible and potentially useful.…”
Section: Discussionmentioning
confidence: 87%